Auditee Satisfaction and Compliance: The Mediating Role of Perceived Service Quality concerning Malaysian SMEs - Ismail, Ashari; Bakri, Muhammed Hariri (The journal of contemporary issues in business and government, 2021)
Audit firms must meet the needs of their auditees to achieve sustainable development. The paper aims to analyze the role of auditee satisfaction perceived service quality to affect the compliance variable in auditing service provided by SMPs to SMEs in Malaysia. Data collected via structured questionnaires through email communication. The collected data were analyzed first using descriptive statistics, followed by correlation analysis to establish the mediating effects of perceived service quality between the dependent and independent variables. Lastly, a regression analysis was borne on the model to test the hypotheses. The study found that auditee satisfaction correlates with perceived service quality, while both perceived service quality and auditee satisfaction were a significant relationship towards compliance. The study also showed that perceived service quality as a mediating role between auditee satisfaction and compliance was significantly based on SEM PLS analysis. The research findings are also imperative to scholars, academics, scientists, and researchers by adding to the body of current knowledge on internal audit and risk management. Nonetheless, its sample size limits the study. Therefore, the results do not represent the whole business organization because they determine Malaysian Smalls and Medium Enterprise, focusing only on retails and wholesales.